2006
DOI: 10.4314/ajtcam.v3i3.31162
|View full text |Cite
|
Sign up to set email alerts
|

Potential protective effect of some plant extracts against carbon tetrachloride – induced hepatotoxicity

Abstract: Plantago major seeds, Diplotaxis acris and Schouiwa thebaica methanol extracts were evaluated for their potential hepatoprotective effects against carbon tetrachloride induced hepatic damage model. Preliminary phytochemical studies were carried out to elucidate their components. Oral administration of the methanol extract (1000 mg kg -1 ) of Plantago major seeds, Diplotaxis acris and Schouiwa thebaica significantly (P< 0.05) attenuated the CCl 4 -induced hepatotoxicity. This was indicated by the tendency of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…It is concluded that the lowest concentration exhibits a hepatoprotective effect. Atta et al [29] reported similar results. Moreover, the reduction in liver glycogen observed in toxin-treated rats may be associated with the decrease in the number of hepatocytes, which in turn may result in decreased hepatic capacity to synthesise glycogen and consequently a decrease in liver weight.…”
Section: Diclofenac-induced Hepatotoxicitysupporting
confidence: 76%
“…It is concluded that the lowest concentration exhibits a hepatoprotective effect. Atta et al [29] reported similar results. Moreover, the reduction in liver glycogen observed in toxin-treated rats may be associated with the decrease in the number of hepatocytes, which in turn may result in decreased hepatic capacity to synthesise glycogen and consequently a decrease in liver weight.…”
Section: Diclofenac-induced Hepatotoxicitysupporting
confidence: 76%
“…Its antioxidant and free radical scavenging activity are contributed by its total phenol contents, flavonoids and caffeic acid derivatives such as plantamajoside and acteoside [10] . Although the hepatoprotective studies have been done previously, those were done on CCl 4 -induced liver injury and P. major was given prior to CCl 4 exposure [17,18] . Based on the promising effect of P. major on liver injury, we took up the challenge of real case scenario and P. major was given after APAP toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive in vitro and in vivo studies showed its hypoglycaemic effect [12] , haemopoietic activity on the bone marrow and spleen cells [13], antiulcer effect on asprin-induced gastric ulcer [14] , antibacterial effect on Staphylococcus aureus and Escherichia coli and antiinflammatory properties [15,16] . Its hepatoprotective activity against carbon tetrachloride (CCl 4 ) toxicity has been observed [17,18]. Based on the promising effect of P. major on liver injury, the present study was aimed to explore its effect on APAP toxicity and determine the potential protective mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be stated that tarvada roots have shown more potent hepatoprotective activity as a prophylactic and anti-hepatotoxic agent than as a therapeutic agent. Review of the literature revealed that anthraquinone glycosides, such as rubiadin (Rao et al, 2006) and emodin (Bhadauria, 2010), tannins and phenolic compounds (Atta et al, 2006) have potent hepatoprotective activity. Flavone glycosides such as hirsutrin, avicularin, quercetin, rutin (Janbaz et al, 2002) and apigenin (Sayed et al, 2011) have significant antioxidant and hepatoprotective activities.…”
Section: Discussionmentioning
confidence: 99%